Hydrothermal preparation of biochar from lignocellulosic biomass for the practical amendment of heavy metal contaminated wastewater - Ramli, Nazwatul Iman (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2015)
The hydrothermal preparation of biochar from spent coconut kernel has been attempted. The potential of the prepared biochar for the practical treatment of heavy metals contaminated wastewater, specifically copper ions (Cu2+) was examined. The physical and chemical prope11ies of coconut kernel derived biochar (CKB) were evaluated by pore structural analysis, scanning electron microscope, elemental analysis, and Fourier transfonn infrared spectroscopy. The elemental analysis illustrated that the content ofC, 0 , H, N, and S was 65.33%, 20.89%, 5.02%, 8.75%, . and 0.0 l% respectively. Adsorption experiments were carried out by varying the adsorbent dosage, initial metal concentrations and contact time, and pH. Experimental results manifested that the adsorptive removal of Cu2+ increased with increasing the adsorbent dosage, initial concentration and contact time, and pH. Maximum Cu2+ removal was observed at pH 5.5, corresponding to the adsorptive uptake of 2.17 mg/g and ads01vtive removal of 99.65%, respectively. Experimental data were analyzed using Langmuir, Freundlich, and Temkin isotherm models. Adsorption data fitted to the Langmuir model, with the correlation coefficient, R~ and RMSD of 0.999 and 0.151, respectively, anticipated a maximum monolayer ads01vtion capacity for Cu2+ ions of 88.08 mg/g. Thermodynamics analysis suggested that adsorption of Cu2 + onto CKB was feasible and in nature, with the ΔG ֯ of-7.696 kJ/mol to -11.081 kJ/mol, and/1Ha and 65°were 43.61 kJ/mol and- 160.40 J/mol K, respectively. The findings revealed the potential of spent coconut kernel biochar as an eco-friendly biosorbent for the in-situ remediation of water pollutants were best.